Non-invasive estimation of material properties of normal and dissected human ascending aortas in vivo: comparison with the ex vivo tensile experiment - Guo, Xiaoya; Yang, Yi; Wang, Liang; Tang, Dalin; Sun, Haoliang (Frontiers in Bioengineering and Biotechnology, 2026)
ObjectivePatient-specific aortic material properties play a critical role in aortic dissection development. In this study, a non-invasive method was employed to assess the in vivo anisotropic mechanical properties of normal and dissected ascending aortas and compare them with their ex vivo material properties.MethodsBiaxial tensile testing was performed on 10 ascending aortic specimens (five patients with type-A aortic dissection and five donors without aortic diseases), with testing data fitted using anisotropic Mooney–Rivlin models. An iterative algorithm was proposed to determine in vivo aortic material properties by matching systolic and diastolic aortic geometries from echocardiography images with those from computed tomography-based computational models. Three settings of initial guesses of material parameters (M01: subject-specific ex vivo parameters; M02: ex vivo parameters of one subject with median stiffness; M03: a 5% variation applied to M02) were investigated in the iterative algorithm for their influence on in vivo property estimation and effective Young’s moduli along the circumferential (YMc) and axial (YMa) directions.ResultsM01-derived in vivo properties had a maximum relative error of −33.44% in YMc/YMa among 10 subjects compared to ex vivo material properties. The median relative error of YMc was −29.40% for M02. Furthermore, a 5% variation in initial parameters caused less than 1.5% change in the estimated in vivo properties. The anisotropy difference between the initial material guess and real aortic tissue would exert a significant impact on YMa estimation but negligible effects on stress distributions.ConclusionOverall, in vivo material properties estimated using the proposed method exhibited lower YMc values than the experimental results for normal and dissected ascending aortas.